Rudolf Bultmann as historikus - Vorster, Willem S. (Hervormde teologiese studies, 1987)
Rudolf Bultmann as historianThe work of Bultmann has had a rather negative reception in South Africa, partly because of the fact that little attention has been paid to his historical interpretation of the New Testament. Unfortunately his name is linked only to his use of philosophical categories in Biblical interpretation. After a few remarks about his early study years and the ideas which framed his later research, the article deals with his work as historian. First he is treated as a historian of religion and then as a literary historian. An attempt is made to understand and describe his views in his contemporary context. The description is done within the framework of the academic context in which he received his training, and the scientific circle in which he performed his academic activities. In conclusion a few remarks of evaluation are made.